SAGE III/ISS aerosol/cloud categorization and its impact on GloSSAC - M. Kovilakam; M. Kovilakam; L. Thomason; T. Knepp (Atmospheric Measurement Techniques, 2023)
The Stratospheric Aerosol and Gas Experiment on the International Space Station (SAGE III/ISS) began its mission in June 2017. SAGE III/ISS is an updated version of the SAGE III on Meteor (SAGE III/M3M) instrument and makes observations of the stratospheric aerosol extinction coefficient at wavelengths that range from 385 to 1550 nm with a near-global coverage between 60∘ S and 60∘ N. While SAGE III/ISS makes reliable and robust solar occultation measurements in the stratosphere, similar to its predecessors, interpreting aerosol extinction measurements in the vicinity of the tropopause and in the troposphere has been a challenge for all SAGE instruments because of the potential for cloud interference. Herein, we discuss some of the challenges associated with discriminating between aerosols and clouds within the extinction measurements and describe the methods implemented to categorize clouds and aerosols using available SAGE III/ISS aerosol measurements. This cloud/aerosol categorization method is based on the results of Thomason and Vernier (2013), with some modifications that now incorporate the influence of recent volcanic/pyrocumulonimbus (PyroCb) events. Herein we describe this new cloud/aerosol categorization algorithm, demonstrate how it identifies enhanced aerosols and aerosol–cloud mixture in the lower stratospheric region, and discuss the impact of this cloud-filtering algorithm on the latest release of the Global Space-based Stratospheric Aerosol Climatology (GloSSAC) data set.